PELATIHAN DAN PEMENTASAN SENI NUSANTARA DALAM BINGKAI MODERASI BERAGAMA DI PASRAMAN PADMA BHUANA SARASWATI YOGYAKARTA (Educemara: Jurnal Pengabdian Masyarakat, 2024)
The existence of Hindu communities outside Bali, especially in DIY, certainly has different access to Hindu education compared to communities in Bali. Moreover, minority life causes the strengthening of religious values to decrease. In the midst of Hindu community life outside Bali, the principles of moderation should be non-negotiable to implement. The methods used in general are faceto-face and practical. Implementation starts from preparation of service activities, delivery of material from resource persons, and provision of artistic equipment. Implementation of activities is carried out by always orienting towards the problems faced and providing solutions. Technically, the materials provided are adjusted to the theme and objectives, then presented to the participants using an interactive method so that the knowledge conveyed by the resource persons can be well received. Furthermore, participants are given assistance in the practice of making puppets, and given direct training for performances. The final stage of the performance is carried out live in front of an audience directly from the local community.
Keywords: Training, Performance, Indonesian Arts and Moderation